Design and usability of learning objects applied in graphic expression - Melian‐Melian, Juan A.; Martin‐Gutierrez, Jorge (Computer applications in engineering education, 2018)
The application of ICT in the field of teaching has meant that learning objects can be used to fulfill an important role in the student‐centered learning process that is being widely promoted across the European Higher Education Area (EHEA). For this study, learning objects were designed as a resource to support teaching and encourage autonomous learning practices in the subject of Graphic Expression belonging to the Architecture Degree. An analysis of their application was performed that involved evaluating the “usability” ratings of students who tested the learning objects. Survey results reveal positive scores were consistently awarded to all three usability components (effectiveness, efficiency, and satisfaction), indicating receptiveness to said learning objects on the part of students. This positive feedback has proven encouraging with regards to continuing with the design and development of new learning objects, and the study of their application in other areas.